The Little Data Book on External Debt 2010 - World Bank (Washington, D.C. The World Bank, 2010)
The Little Data Book on External Debt provides a quick reference for users interested in external debt stocks and flows, major economic aggregates, key debt ratios, and the currency composition of long-term debt for all countries reporting through the Debtor Reporting system. A pocket edition of Global Development Finance 2010, Summary and Country Tables, it contains statistical tables for 135 countries as well as summary tables for regional and income groups.
Description based on print version record.
Keywords: Bankruptcy and Resolution of Financial Distress; Conflict and Development; Debt Markets; Deposit Insurance; External Debt; Finance and Financial Sector Development; Health Systems Development and Reform; Health, Nutrition and Population; International Economics & Trade; Post Conflict Reconstruction